ANALISIS SISTEM PENJADWALAN SHIFT DAN LIBUR KERJA DALAM OPERASIONAL DAPUR CAN NGOPI - Wenston, Darren; Irfan, Muhammad; Sanjaya, Rendi David (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study examines the shift and leave scheduling system in the kitchen operations of Can Ngopi, an educational-based culinary business operated by students in the Gading Serpong area. The significance of this research lies in evaluating the effectiveness of scheduling systems within a semi-professional environment, where students serve not only as operational staff but also as learners of managerial practices. This study employs a descriptive qualitative method, with data collected through direct observation and semi-structured interviews with the General Manager, kitchen leader, and students involved in kitchen shifts. Data analysis was conducted using thematic analysis to identify patterns and themes from the field findings, providing an in-depth understanding of the scheduling dynamics. The results indicate that although the existing system functions adequately, it still faces challenges such as last-minute shift exchanges, insufficient rest periods, and complaints about unfair leave distribution. In conclusion, while the current system offers educational value, further improvements such as scheduling digitalization and periodic evaluations are recommended to enhance the efficiency and fairness of student-based kitchen operations in the future.